2016
DOI: 10.1097/bot.0000000000000570
|View full text |Cite
|
Sign up to set email alerts
|

Infection and Nonunion After Fasciotomy for Compartment Syndrome Associated With Tibia Fractures: A Matched Cohort Comparison

Abstract: Prognostic level III. See Instructions for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 19 publications
0
43
0
3
Order By: Relevance
“…p values on correlations with other variables as stated in the method section can be found in Table 2 . Although the distribution of these factors was similar in our groups, fasciotomy and open fractures were already identified as possible confounders based on the literature (together with fracture type) [ 21 24 ]. In bivariate analysis, these two variables showed relatively high correlations with fracture healing ( R = 0.319 and 0.239, respectively).…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…p values on correlations with other variables as stated in the method section can be found in Table 2 . Although the distribution of these factors was similar in our groups, fasciotomy and open fractures were already identified as possible confounders based on the literature (together with fracture type) [ 21 24 ]. In bivariate analysis, these two variables showed relatively high correlations with fracture healing ( R = 0.319 and 0.239, respectively).…”
Section: Resultsmentioning
confidence: 75%
“…Data on body mass index (BMI), injury severity score (ISS), smoking, non-steroidal anti-inflammatory drugs (NSAID) use, steroid use, neurological trauma, presence of other orthopaedic injuries, infections requiring surgery, fixation treatment and reaming or non-reaming in IM nailing surgery were retrieved from medical records. Since previous studies have identified fracture type, fasciotomy and open fractures as clear risk factors for impaired healing [ 21 24 ], these risk factors were also included in the analysis. Smoking was scored positive if patients smoked during fracture healing or within 6 months before trauma, all regardless of quantity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although necessary, they can be associated with significant morbidity and complications such as skin necrosis, dehiscence after closure, need for grafting procedures, infection, and extended hospital stays. Overall complication rates after fasciotomy have been reported as high as 30% with infection rates reaching up to 20% [7,8]. Our patient had multiple risk factors (myonecrosis at time of fasciotomy, delayed fasciotomies, previous antibiotic exposure) for infection and despite appropriate management, he developed a wound infection due to enterococcus faecalis.…”
Section: Discussionmentioning
confidence: 76%
“…In a separate investigation, Blair et al compared groups with tibia fractures and those with tibia fractures requiring fasciotomy for acute compartment syndrome for rates of delayed union, nonunion, and infection. Their results yielded a 5-week increase in time to union, fourfold greater risk of nonunion, and fivefold greater risk of infection in tibia fractures requiring fasciotomies [22]. There are also substantial increases in the length of hospital stay and total cost associated with the need for fasciotomies to treat ACS [23].…”
Section: Leg Compartment Syndromementioning
confidence: 99%